Experimental investigation of prefabricated steel-truss waffle slab under flexural loading. Issue 2 (January 2020) - Xie, Qun; Xue, Song; Liang, Zhen-hua; Lin, Ming-qiang
A novel type of prefabricated steel-truss waffle slab has been proposed in this article, and compared with traditional waffle slab, there are several typical characteristics of this floor system, including welded steel wire mesh laid in top concrete wythe, orthogonal steel trusses used to reinforce concrete ribs, and foamed concrete blocks filled among the ribs with the purpose of heat insulation and fire resistance. A special template system is adopted for the installation and concrete cast of prefabricated steel-truss waffle slab. All steel segments in prefabricated steel-truss waffle slab are precast and then assembled to form steel system in site. In order to investigate the structural behavior of prefabricated steel-truss waffle slab, two full-scale specimens with different aspect ratio have been experimentally studied under flexural load. The results obtained from the tests have been discussed and analyzed in the context of ultimate flexural load, cracking pattern and failure mode, load–deflection relationship, and load–strain relationship. The experimental results showed that the ultimate load-bearing capacity of prefabricated steel-truss waffle slab has greatly been influenced by the punching shear failure at the rib joints. Three crack types, such as flexural cracks, tensile cracks, and interface cracks, have been exhibited in the final failure of prefabricated steel-truss waffle slab. The deflection development at slab center has presented a four-stage behavior. The significant effect of aspect ratio has also been verified by strain analysis. A computer program has been developed according to the modified structural design method proposed in this article, and the comparison indicated a good agreement between experimental data and theoretical results.